Vegetation greening and climate change respectively regulates the long-term trend and interannual variability in evapotranspiration over the Loess Plateau since the 21st century - Tan, Qiaoyin; Hua, Ting; Zhao, Haichen; Zhou, Peiye (Frontiers in Ecology and Evolution, 2025)
Since the 21st century, large-scale afforestation projects on the Loess Plateau have resulted in significant vegetation greening, contributing to ecosystem restoration and enhanced soil conservation. However, these efforts have also led to soil aridification, declining groundwater levels, and reduced terrestrial water storage. These negative consequences are primarily attributed to increases in evapotranspiration (ET), which has augmented water consumption. Despite these findings, the underlying mechanisms driving ET variations remain contentious due to the complex interplay of multiple factors. In this study, we employed a logical attribution method, which attributes vegetation changes predominantly to anthropogenic activities (e.g., reforestation or land-use changes), while directly linking changes in climatic factors (e.g., temperature and precipitation) to climate change. We separately examined the contributions of long-term trends and interannual variability in ET to reveal distinct driving forces. Between 2000 and 2022, approximately 80% of areas showing significant changes in ET and its components were directly influenced by vegetation greening, particularly in the central part of the Loess Plateau, where restoration efforts were most prominent. In contrast, only around 20% of these changes were attributable to climate change and other factors. After removing long-term trends, interannual variations in ET were found to be more closely associated with climatic factors (temperature and precipitation), especially in arid and semi-arid regions. This indicates that climate is the dominant factor driving interannual variations in ET across the Loess Plateau. Our findings contribute to a deeper understanding of the water cycle dynamics in the context of large-scale vegetation restoration on the Loess Plateau. These insights provide a scientific foundation for policymakers to evaluate the environmental impacts and potential water-related risks associated with ecological restoration projects.